RADIOLOGY OF FISH BONE FOREIGN-BODIES IN THE NECK - Carr, A (1987)
It is common practice for cervical X-rays to be taken of patients who claim to have a fish bone lodged in their throat. Not all fish bones are detectable on X-ray. Two cases are presented of patients who had normal X-rays and were subsequently found to have fish bones in the pharynx. The bones of 17 common species of fish bones have been X-rayed against a cadaver neck. A table showing the relative radiopacity of the bones of these species is given as an aid in their detection.